2019
DOI: 10.1080/21645515.2019.1634992
|View full text |Cite
|
Sign up to set email alerts
|

Emerging infectious disease laboratory and diagnostic preparedness to accelerate vaccine development

Abstract: Rapid vaccine development in response to an outbreak of a new emerging infectious disease (EID) is a goal targeted by public health agencies worldwide. This goal becomes more complicated when there are no standardized sets of viral and immunological assays, no accepted and well-characterized samples, standards or reagents, and no approved diagnostic tests for the EID pathogen. The diagnosis of infections is of critical importance to public health, but also in vaccine development in order to track incident infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This situation is no different in China, which produces many publications, with little evidence of international collaboration. One reason for this may be that there are currently few countries capable of carrying out relevant research in the field of infectious disease (14), which may in turn be due to the high costs in maintaining the strict quality control and biosafety measures required to operate an infectious disease research laboratory (15,16). Despite this, network collaboration is increasing, and has made it easier to carry out multi-center research on many common diseases, rare diseases, and infectious diseases (17).…”
Section: Discussionmentioning
confidence: 99%
“…This situation is no different in China, which produces many publications, with little evidence of international collaboration. One reason for this may be that there are currently few countries capable of carrying out relevant research in the field of infectious disease (14), which may in turn be due to the high costs in maintaining the strict quality control and biosafety measures required to operate an infectious disease research laboratory (15,16). Despite this, network collaboration is increasing, and has made it easier to carry out multi-center research on many common diseases, rare diseases, and infectious diseases (17).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a study found that increasing testing and hospital beds, as well as improving government effectiveness, are associated with lower mortality rates ( Liang et al, 2020 ). Although the timely development of effective vaccines has been possible in the past ( Kieny, 2018 ; Peeling et al, 2019 ; Roberts, 2019 ), even in the case of the COVID-19 ( Krammer, 2020 ), funding poses a major barrier for widespread vaccination ( Gouglas et al, 2018 ). Furthermore, socio-economic disparities accentuate the challenges in vaccine development, manufacturing, and delivery at the local and global level ( Plotkin et al, 2017 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…Roberts discusses the challenges facing immunology laboratories involved in the conduct of clinical trials for emerging infectious diseases (EID). 8 In this monograph, the tenets previously introduced for ZIKV 9 are further explored for a generic EID. There is the need for standardized reference reagents, control samples, and diagnostic assaysthat for EIDs might not exist at the time that clinical trials commence.…”
Section: Framework Considerations For Vaccine Developmentmentioning
confidence: 99%